2009
DOI: 10.1677/joe-08-0505
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin 2 induces potent long-lasting inhibition of cardiac sympathetic drive despite baroreflex activation in conscious sheep

Abstract: Emerging evidence suggests that the urocortin (UCN) peptides contribute to pressure and volume regulation with possible involvement in the pathophysiology of cardiovascular disease. We have recently reported that i.v. UCN1 potently inhibits cardiac sympathetic nerve activity (CSNA) in normal sheep. However, little is known about possible interactions between UCN2 and the sympathetic nervous system. Accordingly, we have examined the effects of i.v. UCN2 on CSNA, hemodynamics, and plasma catecholamines in normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The impressive and persistent improvements in CO observed in the HF animals in the current study likely reflect Ucn2's potent inotropic activity 5,17 given the concomitant rise in dP/dt(max), as well as falls in cardiac afterload (CTPR). The CO increase presumably contributed to the marked decline in LAP (Ͼ15 mm Hg drop by day 4), although the lusitropic 5 and venodilator actions of the peptide (the latter decreasing circulatory filling pressures) 18 may also have participated.…”
Section: Discussionmentioning
confidence: 62%
“…The impressive and persistent improvements in CO observed in the HF animals in the current study likely reflect Ucn2's potent inotropic activity 5,17 given the concomitant rise in dP/dt(max), as well as falls in cardiac afterload (CTPR). The CO increase presumably contributed to the marked decline in LAP (Ͼ15 mm Hg drop by day 4), although the lusitropic 5 and venodilator actions of the peptide (the latter decreasing circulatory filling pressures) 18 may also have participated.…”
Section: Discussionmentioning
confidence: 62%
“…Effects of urocortin 2 (red) and urocortin 3 (blue) last 40-60 min after cessation of dose 3 (D3) before returning to baseline. At the doses used, urocortin 3 caused a greater increase in cardiac output compared with urocortin 2 in patients with heart failure (P < 0.0001) but not healthy subjects (P = 0.48) of cardiac sympathetic nerve activity [SNA] [27,28], often overactive in patients with heart failure. Although Ucn2 has been reported to increase skeletal muscle SNA in humans [29], this should not necessarily be seen as a discrepant finding as SNA responses typically are regionally differentiated.…”
Section: Figurementioning
confidence: 99%
“…On the other hand, several trials in which Ucns are being used to treat experimental [5964] and human cardiac failure [65] are ongoing and have provided some potentially beneficial results, because Ucn I may exert inotropic actions that may play a key role in the treatment of cardiac failure. And Ucn II may also improve the renal function [66], and sympathetic activity in heart failure [30], synthetic Ucns, or nonpeptide CRF receptor agonists may prove useful for the treatment of cardiac failure.…”
Section: Clinical Use Of Ucns To Treat Cardiovascular Diseasementioning
confidence: 99%
“…[22, 26, 27]. The other reported beneficial actions of Ucn I on the heart is to reduce infarct size in vivo, improve intracellular calcium handling [28], increase the ventricular fibrillation threshold [29], reduce the occurrence of arrhythmias [28], and inhibit efferent cardiac sympathetic nerve activity [30]. These facts indicated that Ucn I and its analogs may have beneficial actions in the treatment of cardiac diseases as well as play certain roles in cardiac diseases.…”
Section: Introduction: Overview Of Corticotropin-releasing Hormonementioning
confidence: 99%